A new ideological classification of the Brazilian political parties - Bolognesi, Bruno (2021)
As long as democratic politics modify itself, perception on the belonging political parties’ also do. The paper’s main purpose is to bring in a new and updated ideological classification of Brazilian political parties. Data elicited from political scientists through a survey in 2018 asked them to position each party on the left-right continuum and, additionally, regarding their major objective, to pursue votes, government positions or policy issues. Our findings point out to a centrifugal trend on party system pushing most of parties to the right. Furthermore, we show a prevalence of patronage and clientelistic parties who rank in first the votes-positions dyad rather policy.